2022
DOI: 10.1007/s43390-022-00479-8
|View full text |Cite
|
Sign up to set email alerts
|

Subjective perception of spinal deformity after selective versus non-selective fusion of Lenke 1C curves

Abstract: Purpose To assess the self-image perception and the Quality-of-Life (QoL) in female adolescents, with Lenke 1C scoliosis curves, treated with selective versus non-selective posterior spinal instrumentation and fusion (PSF). Methods Patients undergoing PSF for idiopathic adolescent scoliosis (AIS) were recruited and divided into two groups: patients managed with selective thoracic fusion (STF) were included in Group A, whereas patients treated with non-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…This finding is tought to be due to small number of patients in groups. 36 In conclusion when the flexibility in the preoperative bending x-ray is more than 70% (P < .01) and when AVR is equal or less than 2 grades in Lenke 1C and Lenke 2 C curves, STF provides satisfactory clinical and radiological SLCC at a mean follow up of 12.2 (minimum 8 and maximum 23) years. In addition, our study showed that a flexibility rate of the lumbar curve greater than 70% and a preoperative AVR grade equal to or less than 2 grades are more important criteria than the preoperative lumbar curve magnitude and preoperative AVT distance in the decision making of STF and for the prevention of coronal plane decompensation in Lenke 1-2 C curves.…”
Section: Discussionmentioning
confidence: 81%
“…This finding is tought to be due to small number of patients in groups. 36 In conclusion when the flexibility in the preoperative bending x-ray is more than 70% (P < .01) and when AVR is equal or less than 2 grades in Lenke 1C and Lenke 2 C curves, STF provides satisfactory clinical and radiological SLCC at a mean follow up of 12.2 (minimum 8 and maximum 23) years. In addition, our study showed that a flexibility rate of the lumbar curve greater than 70% and a preoperative AVR grade equal to or less than 2 grades are more important criteria than the preoperative lumbar curve magnitude and preoperative AVT distance in the decision making of STF and for the prevention of coronal plane decompensation in Lenke 1-2 C curves.…”
Section: Discussionmentioning
confidence: 81%
“…The demographic data of our group of patients with an average age of 14.71 years and a female predominance, as well as the average preoperative Cobb angles and curve types, are comparable to data reported in other recent investigations. [8][9][10][11][12][13][14][15][16][17][18][19] This seems to indicate that our study population may be representative.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, other investigations showed that SF compared with NSF led to a minor correction of the nonstructural curves. 10,11 According to the subjective perception of the patients, Bizzoca et al showed that although the SF provides better functional outcomes, female patients receiving SF reported a worse perceived body image compared with patients treated with NSF. 12 Surgical correction from the posterior can be performed by an all screws technique (AS), hybrid technique with screws and hooks (HTH), or hybrid technique with screws, hooks, and tapes (HTHT).…”
Section: Introductionmentioning
confidence: 99%
“…Scoliosis is a three-dimensional spine deformity defined by a Cobb angle greater than 10 • with combined vertebral rotation [1].…”
Section: Introductionmentioning
confidence: 99%
“…It typically occurs between the ages of 10 and 18, with no identifiable cause or underlying pathology [2,3]. This condition affects approximately 2-4% of adolescents, with a higher prevalence in females than males [1][2][3].…”
Section: Introductionmentioning
confidence: 99%